Angiotensin Converting Enzyme (ACE) Inhibitory Activity of Crude and Fractionated Snakehead Fish (Channa striata) Fillet Extract - Setyani Budiari; Ekowati Chasanah; Maggy Thenawidjaja Suhartono; Nurheni Sri Palupi (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
The existence of endogenous bioactive protein or peptide with angiotensin-converting enzyme (ACE) inhibitory activity in snakehead fish fillet is promising to be investigated. The purposes of this research were to extract ACE inhibitory endogenous protein or peptide from snakehead fish fillet and to fractionate the active compounds using ultrafiltration. The extraction employed two solvents, i.e. aquadest and 50% ethanol. Fractionation was conducted using ultrafiltration membranes of 10,000; 5,000 and 3,000 Molecular Weight Cut Off (MWCO) to separate the protein or peptide into the sizes of 10 kDa, 5-10 kDa, 3 -5 kDa and 3 kDa. The parameters observed were protein and peptide content, ACE inhibitory activity (in vitro) and also protein and peptide profiles. The result revealed that the snakehead fish fillet contained ACE inhibitory endogenous bioactive protein or peptide. The 50% ethanol was more effective in extracting peptide of 10 kDa than the aquadest. Yet, the aquadest was better in extracting higher molecular weight protein of 10 kDa than the 50% ethanol. The fraction of 3 kDa by aquadest had the highest ACE inhibitor activity per g protein (7.85% inhibition of ACE per g protein). Thus, the fraction of 3 kDa aquadest is the most promising option for further research and development of natural anti-hypertension compound. From the result, snakehead fish fillet was potential to be utilized as a functional food as well as functional ingredient to fight hypertension.